Apoptosis effects of Luvunga scandens leave extracts and its compound on human skin cancer A431 cell line - Shaban, Sama Naziyah (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Skin cancer is reported as one of the most common types of cancer with increasing numbers of occurrence. Luvunga scandens is one of the medicinal plants found in Malaysia. This plant is known to possess many bioactivities and general health effects, yet its anti-proliferative effect is generally under reported and need to be scientifically evaluated. The aim of this study is to evaluate the anti-proliferative and apoptotic effects of Luvunga scandens plant leaves against human skin cancer cell line. MTT assay was used to test the cytotoxicity effect of L. scandens on human skin carcinoma cells together with its effect against normal cell lines (HaCaT and HDF). Scratch assay was carried out to evaluate the cell growth. The morphological changes of L. scandens treated skin cancer cells was confirmed by scanning electron microscopy, and the apoptotic effect of the plant against skin cancer cells was tested using caspase 3/7 assay, followed by cell cycle analysis done using a flow cytometer on skin cancer cells. Western blot was preformed to investigate the anti-carcinogenic effect of L. scandens against human skin cancer cells. The results showed that the extract and a compound 3-oxotirucalla-7,24-dien-21-oic acid possesses cytotoxic effect against skin cancer cells, and it was no cytotoxic activity in both of HaCaT and HDF cells. The scanning electron microscopy results demonstrate that L. scandens treated cells showed an overall change in the cell shape, alteration of surface morphology, absence of microvilli and appearance of blebs. Caspase 3/7 assay results showed that L. scandens dichloromethane (DCM) extract exhibited the highest level of apoptosis against skin cancer cells. For cell cycle analysis, all the L. scandens treated skin cancer cells show high readings in the sub-G1 phase. For western blot the L. scandens extract and compound show high apoptosis effects against human skin cancer cells. This in vitro study has proven that L. scandens plant exhibit anti-proliferative effects against human skin cancer cell hence, it can be considered as a promising natural source for anticancer therapy.